Biobased polymer and surfactant for enhanced recovery of heavy oil - Hassan, Mifzal (2021)
Rising energy demand, coupled with a decline in conventional oil reserves, has led to increase interest in heavy oil recovery in recent years. Chemical enhanced oil recovery methods have become an efficient and economical option for heavy oil reservoirs where thermal methods cannot be applied like in thin deep reservoirs. The purpose of this study is laboratory scale investigation of new environmentally friendly biopolymer and biosurfactant for heavy oil recovery application. The biopolymer and biosurfactant were Guar gum and Coco glycoside, respectively. To determine the optimum concentration of biopolymer and surfactant system for tertiary flooding application, rheological characterization study was conducted using Brookfield RST Rheometer and interfacial tension studies was carried out by using Kruse force Tensiometer at room temperature (25°C). The performance of these optimum formulations was determined by conducting four different injection schemes heavy oil displacement tests in artificial glass bead (125 μm to 850 μm) flooding models saturated with engine as the heavy oil phase and brine (30,000 ppm) representation formation water. The injection schemes for flooding tests were single polymer, single surfactant, sequential polymer - surfactant and polymer surfactant combine slug at optimum formulation concentration. Findings of the characterization tests shown that that the optimum concentration of biopolymer and biosurfactant were 6000 ppm concentration and minimum 1.7mN/M interfacial tension at 920 ppm concentration, respectively. Experimental Results also shown that salinity has no impact upon biopolymer shear viscosity while it improves interfacial activity of biosurfactant. Oil displacement tests shown that combine polymer –surfactant slug give high incremental oil recovery (27.8 % IOIP) compared to polymer injection scheme (21.5% IOIP), polymer -surfactant sequential injection scheme (18.4% IOIP) and surfactant injection scheme (9.2% IOIP) that indicated their good synergy in compound flooding after water flooding. Based upon flooding experiments findings it was revealed that main mechanism for increasing incremental oil recovery factor is mobility ratio improvement of displacing fluid compared to IFT reduction. The polymer and surfactant used in this study are natural plant derived materials and show great potential for use in future heavy oil enhanced oil recovery operations.